(untitled) (Konferensiyalar | Conferences, 2024)
This article investigates linguistic and pragmatic aspects that are used in media discourse especially newspaper texts. It presents a comparative analysis of the linguistic and pragmatic features of newspaper texts in English and Uzbek languages, focusing on their similarities and differences. Lingusitic analysis focuses on lexical choices and syntactic features of newspaper texts. While from pragmatic point of view, the study examines how newspaper texts employ various pragmatic strategies to achieve communicative goals. This study offers a comprehensive understanding of the similarities and differences in the construction and interpretation of news across languages